Penerapan Model Pembelajaran Teknik Two Stay Two Stray dalam Meningkatkan Ketrampilan Berbicara tentang Berita Kelas VIIIA SMPN Satu Atap Kujiratu - Marlyani Gewe; Labu Djuli; Semuel Hajai Nitbani (Student Research Journal, 2026)
This study aimed to improve students' speaking skills in news text learning through the implementation of the Two Stay Two Stray (TSTS) learning model. The research employed Classroom Action Research (CAR) conducted in two cycles involving Grade VIII students of SMP Negeri Satu Atap Kujiratu. Data were collected through observation, performance assessment, and learning outcome tests. The findings indicated that the application of the TSTS model contributed positively to students’ speaking skills and learning outcomes. In Cycle I, 16 students achieved mastery learning, while 13 students did not, with a class average score of 43.15. In Cycle II, learning outcomes improved, with 18 students achieving mastery learning and 11 students not yet meeting the minimum criteria, resulting in an average score of 73.11. The improvement was supported by increased student participation, confidence in expressing ideas, and collaborative interaction during group discussions. The study concludes that the Two Stay Two Stray learning model is effective in enhancing students’ speaking skills in news text learning and can serve as an alternative cooperative learning strategy in Indonesian language instruction.